PELATIHAN MANAJEMEN PENGELOLAAN MADRASAH BERBASIS KURIKULUM CINTA DI MADRASAH TSANAWIYAH AL AZHAR AJUNG JEMBER - Badrun Fawaidi Badrun Fawaidi; Hafid; Sa'adatu Mukarromatil Arifah (P3M Sekolah Tinggi Agama Islam Miftahul Ulum, 2026)
This article aims to analyze in depth the process and implications of Curriculum-Based Madrasah Management Training at Madrasah Tsanawiyah as a response to the need for value-based management strengthening. The research uses a qualitative approach with a case study type combined with the Asset-Based Community Development (ABCD) method. Data were collected through semi-structured interviews, participatory observation, and documentation studies of 12 participants consisting of school principals, vice principals, teachers, and training teams selected through purposive and snowball sampling. Data analysis was conducted using Miles and Huberman's interactive model through reduction, presentation, and thematic conclusion drawing. The results of the study reveal three main themes: (1) internalization of the value of love in the vision and culture of the organization, (2) strengthening of participatory leadership based on community assets, and (3) transformation of managerial practices through collective reflection. These findings confirm that training based on the Love Curriculum not only improves technical competencies, but also shapes value awareness and institutional collaboration. Theoretically, this study enriches the study of value-based Islamic education management; practically, it provides recommendations for policy makers and training institutions to develop participatory and sustainable programs